MENINGKATKAN HASIL BELAJAR KIMIA DENGAN MODEL MISSOURI MATHEMATIC PROJECT (MMP) BERBASIS TEKNOLOGI INFORMASI PADA SISWA KELAS XI IPA SMA NEGERI 9 PALU - Alamsyah Alamsyah (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Dampal Selatan, 2018)
It has been conducted a research where that on the model of Missouri Mathematic Project (MMP) based on information technology to improve learning outcomes chemistry in grade XI IPA at SMAN 9 Palu has been implemented from January 2016 to February 2016. This study aims to: improve learning outcomes of students with a chemistry models learning Missouri Mathematic Project (MMP) based on Information Technology in grade XI IPA at SMAN 9 Palu. The method used is descriptive method with data retrieval technique using sheets achievement test consisting of cycle 1 and cycle 2. Type this research is classroom action research (PTK). Subjects were students of class XI IPA 1 SMAN 9 Palu totaling 29 students composed of 7 men and 22 women. The results showed that the learning outcomes of students who complete the first cycle were 13 people, while in the second cycle as many as 27 people. Classical absorption capacity on the first cycle is 67,24%, while in the second cycle is 87,93%. Mastery learning classical at the first cycle is 44,83% and the second cycle is 93,10%. Improving student learning outcomes after the implementation of the first cycle of action including very high category with a percentage of 98,98% and after the implementation of the second cycle, including low category with a percentage increase of 30,77%. The results of observation activities of teachers in the first cycle values ​​obtained 90,79% are excellent, student activities is 91,67%, very good category. The results of the activities of teachers observation second cycle is 96,62%, excellent category, activity of students in the second cycle is 96,97%, very good category. Based on these results it can be concluded that the learning model Missouri Mathematic Project (MMP) Information Technology can improve student learning outcomes in subjects chemistry class XI IPA 1 SMAN 9 Palu.